The Effectiveness of Dietary Fucoidan Compared to the Combination of Fucoidan with Turmeric on the Growth of African Catfish (Clarias Gariepinus) - Cahyono Purbomartono; Rini Emawati; Dini Siswani Mulia; Haryanto Haryanto (UM Purwokerto Press, 2023)
To meet the needs of fish consumption for the community, African catfish are cultivated intensively. African catfish cultivation is carried out intensively with high stocking density, but some disadvantages inhibit growth. To support growth, it is done by giving a combination of fucoidan supplements with turmeric. Fucoidan and turmeric are known to increase fish growth, but there are no reports of using a combination of fucoidan and turmeric given in feed to increase fish growth. Therefore, this study wants to determine the effect of fucoidan supplementation with turmeric on the growth of African catfish. The method used was a completely randomized design with treatment B: (400 mg fucoidan + 1350 mg turmeric extract) kg-1 feed, C: (800 mg fucoidan + 1200 mg turmeric extract) kg-1 feed, D: (1200 mg fucoidan + 1050 mg of turmeric extract) kg-1 of feed and control (A), each with 4 replications. The parameters observed were weight and length gain, survival growth rate (SGR), feed conversion rate (FCR), and feed efficiency (FE). Data were analysed using analysis of variance (ANOVA) at the 95% confidence level and continued with Duncan's Multiple Range Test (DMRT). The results showed that the combination of fucoidan supplementation with turmeric significantly increased (p <0.05) weight and length growth, SGR, FCR, and FE. The addition of fucoidan supplements with turmeric can be used to cultivate African catfish with an optimal dose (1200 mg fucoidan + 1050 mg turmeric extract) kg-1 feed.